Evaluation of prenatal and postnatal diagnostic criteria for twin anemia‐polycythemia sequence. (4th January 2015) - Veujoz, Marine; Sananès, Nicolas; Severac, François; Meyer, Nicolas; Weingertner, Anne‐Sophie; Kohler, Monique; Guerra, Fernando; Gaudineau, Adrien; Nisand, Israël; Favre, Romain
Abstract Objective The aim of this study is to analyze the relevance of the prenatal and postnatal diagnostic parameters of twin anemia‐polycythemia sequence (TAPS). Methods Diagnostic data of all cases of TAPS followed in our institution between 2006 and 2013 were reviewed. Statistical analyses were conducted using Bayesian methods. Results Twenty cases of TAPS were included. We found a relationship between the hemoglobin level and the middle cerebral artery peak systolic velocity (coefficient −0.25 [−0.34, −0.15], Pr(coef < 0) = 99.99%). Sensitivity and specificity of the prenatal diagnosis were 71% and 50%, respectively, regarding the correspondence with postnatal diagnosis. There was no correlation between the number [odds ratio (OR) = 0.89 [0.72, 1.10], Pr(OR > 1) = 14.8%)], the mean diameter (OR = 0.98 [0.32, 3.06], Pr(OR > 1) = 48.9%), or the total diameter (OR = 0.79 [0.36, 1.53], Pr(OR > 1) = 26.3%) of arteriovenous anastomoses and the severity of TAPS. Conclusion Middle cerebral artery peak systolic velocity is a reliable tool for estimating the hemoglobin level in cases of TAPS. The correspondence between prenatal and postnatal diagnosis is imperfect. Further studies are required to evaluate opportunity of widening postnatal diagnostic criteria. © 2014 John Wiley & Sons, Ltd.